Tingkat residu pestisida dalam daging kelinci peranakan New Zealand White yang diberi pakan limbah pertanian kubis (Brassica oleracea) - S. Sulistyaningsih; Sri Minarti; Osfar Sjofjan (Faculty of Animal Science, Universitas Brawijaya, 2013)
ABSTRACT: The study examines fat and water content, and the level of pesticide residues in rabbit’s meat which were fed cabbage leaves waste. The materials used in the study were 12 New Zealand White rabbits raised from 1.5 to 3 months of age. Those rabbits were divided into 3 different groups (large, medium and small) based on their initial body weight. The laboratory test shows there were several types of pesticide residues in the cabbage leaves and rabbit’s meat namely endosulfan, profenofos and chlorpyrifos. The lowest pesticide residues were found at small rabbit’s meat groups. In contrast, the fat content as well as the water content was found high at large rabbit’s meat groups. Keywords: rabbits, cabbage, residues, fat content and water content